GENETIC VARIABILITY AND ASSOCIATION ANALYSIS FOR YIELD AND ITS COMPONENTS IN F YIELD AND ITS COMPONENTS IN F2 AND F3 SEGREGATING GENERATIONS OF THE MAIZE ( TIONS OF THE MAIZE (Zea mays Zea mays L.) CROSS BM125 X BM135 .) CROSS BM125 X BM135 - DEEPU, T. M.; DESHPANDE, S. K .; B. R. MANI (The Bioscan, 2018)
Crop improvement depends on, existence of genetic variability, understanding of traits inter-relations and determining the direct and indirect effects of yield determining factors. The study aimed at estimation of variability and trait associations in F2 and F3 generations of the cross BM-125 (high yielding) X BM-135 (low yielding) and drawn following results. PCV an indicative of environmental influence on the traits was in the range of low to medium for CLN, CGR, KRPC and KPR in both F2 and F3. Whereas, KPR, CWT, TW and GY exhibited high PCV in F2 and F3 which, means these traits are highly influenced and hence, selection based on such traits is not advisable. TW had moderate and high heritability in F2 and F3 respectively therefore, selection based on TW is recommended. CLN, CGR, KPR and CWT showed positive and significant association with grain yield in F2 and F3 . The parents BM125 and BM 135 were also screened for tolerance to the disease, Turcium leaf blight under artificial epiphytotic conditions where, BM125 was found to be susceptible whereas, BM135 was resistant. Present study concludes superior family identification and generation advancement for high yield must be based on CLN, CGR CWT and TW